Chloeia rozbaczyloi, a new species of polychaete (Archinominae: Amphinomidae) and first record of the family for the Nazca Ridge, southeastern Pacific Ocean - Cañete Aguilera, Juan Ivan; Romero, Maria S.; Easton, Erin E.; Mecho, Ariadna; Sellanes, Javier (My University, 2023)
The amphinomid polychaete Chloeia rozbaczyloi sp. nov., collected from seamounts of the Nazca Ridge (NR), northwest of Desventuradas islands, southeastern Pacific Ocean, is described. The new species was observed on only two of seven seamounts surveyed in the area (25.079S, 82.006W, and 25.408S, 81.769W, similar to 220 m depth), being abundant on one of them. Specimens were observed under optical and scanning electron microscopes, and DNA was sequenced (COI, 16S, 18S, and 28S nucleotide alignment). Chloeia rozbaczyloi sp. nov. belongs to the venusta group of Chloeia and is distinguished mainly by: (i) the chromatic pattern of the dorsum (with a single middorsal dark band) and the caruncle (with 16-20 vertical folds and 12 to 14 black spots posteriorly decreasing in diameter), (ii) by the biannulated dorsum of the first ten chaetigers, each with a bean-shaped anterior pseudosegment, (iii) long neuropodial cirri, with a short ceratophore, at chaetiger 2 and reaching chaetiger 6, and (iv) bipinnate branchiae from chaetiger 4, with seven to nine lateral branches arising from the primary axis, each possing five pinnules; branchiae change progressively in size to the posterior end. The ciliated margin of the accessory dorsal cirri suggests a respiratory function that might be relevant considering that both seamounts in which the species was observed could be influenced by low-oxygen waters. DNA results further support that C. rozbaczyloi sp. nov. differs from the other five congeneric taxa (C. bimaculata, C. flava, C. parva, C. pocicola, and C. viridis) for which genetic information is available. This finding constitutes the first report of the genus for Chilean waters, increasing the number of species of Amphinomidae in this area to seven. It also confirms the presence of the family in the NR and increases the number of Chloeia species in the world to 43. The seamounts where the new species have been collected are within the newly created offshore NazcaDesventuradas Marine Park. Information on potentially unique and endemic species, such as the one discussed here, is of utmost importance to preserve special ecological units, address ecosystem services, and implement management measures in the area.
Keywords: fireworm; deep sea; seamount; nazca-desventuradas marine park; chile; archinomidae